A Study of Family Relations in Sam Shepard's Fool for Love: Family as a Falling Myth - Muslim, Elaf Muther (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
Family relations form one of the main themes of Sam Shepard's plays. However, these interactions are not like what is noticed in a traditional family. Fool for Love is a play by Shepard which narrates the story of a sister and brother who used to be in love but now the situation has changed and both are alienated and hurt. The problems that they encounter are the result of their parents' mistakes. By writing such a play, Shepard meant to show how the myth of a good American family can be devastated easily. In other words, it is going to be stated that there is a conflict between the familial themes and the committed doctrine of the modern American family myth in Fool for Love. Hence, this study seeks to analyze this play through Lyotard's notion of the fall of myths in order to conclude how postmodernism has destroyed the notions of life, happiness, and identity. The themes of a cohesive American family, faithfulness, and love have changed into the fragmented and alienated families. It will also be stated that for Shepard, the most noticeable features of a postmodern society include viciousness, disloyalty, desperateness, and separation.